2014
DOI: 10.1371/journal.ppat.1004378
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid Derived Hypoxia Inducible Factor 1-alpha Is Required for Protection against Pulmonary Aspergillus fumigatus Infection

Abstract: Hypoxia inducible factor 1α (HIF1α) is the mammalian transcriptional factor that controls metabolism, survival, and innate immunity in response to inflammation and low oxygen. Previous work established that generation of hypoxic microenvironments occurs within the lung during infection with the human fungal pathogen Aspergillus fumigatus. Here we demonstrate that A. fumigatus stabilizes HIF1α protein early after pulmonary challenge that is inhibited by treatment of mice with the steroid triamcinolone. Utilizin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
73
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(84 citation statements)
references
References 82 publications
7
73
0
Order By: Relevance
“…HIF-1α transcriptional activity is also required for CXCL1 expression in myeloid cells, which mediates the survival of neutrophils in mycosis. 9 In ECs, preformed CXCL1 is stored in vesicles and released on activation by LPA. 6 CXCL1 is immobilized on the endothelial surface and induces proatherogenic monocyte adhesion by binding to its receptor CXCR2.…”
Section: Discussionmentioning
confidence: 99%
“…HIF-1α transcriptional activity is also required for CXCL1 expression in myeloid cells, which mediates the survival of neutrophils in mycosis. 9 In ECs, preformed CXCL1 is stored in vesicles and released on activation by LPA. 6 CXCL1 is immobilized on the endothelial surface and induces proatherogenic monocyte adhesion by binding to its receptor CXCR2.…”
Section: Discussionmentioning
confidence: 99%
“…Shepardson and colleagues found that mice with myeloid HIF-1α deficiency are more susceptible to pulmonary challenge with Aspergillus fumigatus, are defective in fungal clearance, and exhibit decreased lung neutrophil numbers. These phenotypes can be partly attributed to decreased production of CXCL1 and increased neutrophil apoptosis (148). Contradictory to the finding that macrophage HIF-1α prevents airway allergy, a study by Byrne and colleagues suggests that development of airway allergy is dependent on macrophage HIF-1α.…”
Section: Hifs In Myeloid Cellsmentioning
confidence: 99%
“…Hypoxia-inducible factor 1 (HIF-1)α is a host transcription factor that mediates multiple functions during periods of low oxygen. A. fumigatus has recently been shown to stabilize HIF-1α in the lung, a process interrupted by CT [66] . Mice with HIF-1α deletion in myeloid cells rapidly succumb to IA as a result of impaired neutrophil recruitment to the lungs and enhanced neutrophil apoptosis [66] .…”
Section: Autophagymentioning
confidence: 99%
“…A. fumigatus has recently been shown to stabilize HIF-1α in the lung, a process interrupted by CT [66] . Mice with HIF-1α deletion in myeloid cells rapidly succumb to IA as a result of impaired neutrophil recruitment to the lungs and enhanced neutrophil apoptosis [66] . A recent study documented that mice deficient in CXCR2 and those immunosuppressed with corticosteroids display defective clearance of A. fumigatus from the lungs in the presence of increased hypoxia and increased levels of proinflammatory cytokines, including IL-1α and IL-1β [67] .…”
Section: Autophagymentioning
confidence: 99%